Bifidobacterium actinocoloniiforme sp. nov. and Bifidobacterium bohemicum sp. nov., from the bumblebee digestive tract - Killer, J; Kopečný, J; Mrázek, J; Koppová, I; Havlík, J; Benada, O; Kott, T (International journal of systematic and evolutionary microbiology, 2011)
Our previous study, based primarily on PCR-denaturing gradient gel electrophoresis and 16S rRNA gene sequencing, focused on the isolation of four bifidobacterial groups from the digestive tract of three bumblebee species. In that study, we proposed that these isolated groups potentially represented novel species of the family Bifidobacteriaceae. One of the four, Bifidobacterium bombi, has been described recently. Strains representing two of the other groups have been classified as members of the genus Bifidobacterium on the basis of positive results for fructose-6-phosphate phosphoketolase activity and analysis of partial 16S rRNA and heat-shock protein 60 (hsp60) gene sequences. Analysis of 16S rRNA gene sequence similarities revealed that the isolates of the first group were affiliated to Bifidobacterium asteroides YIT 11866(T), B. indicum JCM 1302(T) and B. coryneforme ATCC 25911(T) (96.2, 96.0 and 95.9 % sequence similarity, respectively), together with other bifidobacteria showing lower sequence similarity. Additional representatives of the second group were found to be affiliated to Bifidobacterium minimum YIT 4097(T) and B. coryneforme ATCC 25911(T) (96.0 and 96.3 % sequence similarity) and also to other bifidobacteria with lower sequence similarity. These results indicate that the isolates of the two groups belong to novel species within the genus Bifidobacterium. This observation was further substantiated by the results of partial sequencing of hsp60. On the basis of phylogenetic and phenotypic analyses and analysis of 16S rRNA and partial hsp60 gene sequences, we propose two novel species, Bifidobacterium actinocoloniiforme sp. nov. (type strain LISLUCIII-P2(T) = DSM 22766(T) = CCM 7728(T)) and Bifidobacterium bohemicum sp. nov. (type strain JEMLUCVIII-4(T) = DSM 22767(T) = CCM 7729(T)).
Keywords: DNA bakterií; DNA, Ribosomal; Phylogeny; chaperon hsp60; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Chaperonin 60; Aldehyde-Lyases; aldehydlyasy; RNA ribozomální 16S; Cluster Analysis; zvířata; včely; RNA, Ribosomal, 16S; sekvenční analýza DNA; DNA, Bacterial; Bees; fylogeneze; shluková analýza; ribozomální DNA; Animals; Bifidobacterium; Gastrointestinal Tract; gastrointestinální trakt